Impacts of climate change on the seasonal distribution of migratory caribou - Sharma, Sapna; Couturier, Serge; Côté, Steeve D. (Global Change Biology, 2020)
Arctic ecosystems are especially vulnerable to global climate change as temperature and precipitation regimes are altered. An ecologically and socially highly important northern terrestrial species that may be impacted by climate change is the caribou, Rangifer tarandus. We predicted the current and potential future occurrence of two migratory herds of caribou [Rivière George herd (RG) and Rivière-aux-Feuilles (RAF) herd] under a Canadian General Circulation Model climate change scenario, across all seasons in the Québec–Labrador peninsula, using climatic and habitat predictor variables. Argos satellite-tracking collars have been deployed on 213 caribou between 1988 and 2003 with locations recorded every 4–5 days. In addition, we assembled a database of climate (temperature, precipitation, snowfall, timing and length of growing season) and habitat data obtained from the SPOT VEGETATION satellite sensor. Logistic regression models indicated that both climatic and physical habitat variables were significant predictors of current migratory caribou occurrence. Migratory caribou appeared to prefer regions with higher snowfall and lichen availability in the fall and winter. In the summer, caribou preferred cooler areas likely corresponding to a lower prevalence of insects, and they avoided disturbed and recently burnt areas. Climate change projections using climate data predicted an increased range for the RAF herd and decreased range for the RG herd during 2040–2069, limiting the herds to northeastern regions of the Québec–Labrador peninsula. Direct and indirect consequences of climate change on these migratory caribou herds possibly include alteration in habitat use, migration patterns, foraging behaviour, and demography, in addition to social and economic stress to arctic and subarctic native human populations.